Analisis Kointegrasi Bursa Efek Indonesia, Malaysia dan Singapura: Pendekatan Pair-Case dan Multivariate - Amsal Irmalis; Fajri Hadi (Jurnal Manajemen dan Kewirausahaan, 2020)
This study aims to examine the stock market cointegration between  Indonesia Stock Exchange (IDX),  Malaysian Stock Exchange (Bursa Malaysia) and Singapore Stock Exchange (SGX). The weekly stock indexes covering January 2013 to December 2018 are analyzed using the Johansen testing approach with the Vectorautoregresiv (VAR) framework. This study uses a pair-case and multivariate manner. The results show that multivariate analysis does not show any cointegration between Indonesia, Malaysia, and the Singapore Stock Exchange. However, cointegration exists between the Malaysian and Singapore capital markets. These results confirm that the same results of  bivariate analysis do not always support multivariate testing.https://doi.org/10.26905/jmdk.v8i1.3538